Laparoscopic Sacrohysteropexy for the Management of Uterovaginal Prolapse: a Pilot, Single-Center Experience from Saudi Arabia - Hafedh B; Idris SM; Nadreen F; Banasser AM; Iskandarani R; Baradwan S (Dove Medical Press, 2024)
Bandr Hafedh, Sarah Mohammed Idris, Farah Nadreen, Abdulrhman M Banasser, Radiah Iskandarani, Saeed Baradwan Department of Obstetrics and Gynecology, King Faisal Specialist Hospital and Research Center, Jeddah, Saudi ArabiaCorrespondence: Saeed Baradwan, Email dr.saeed_bardwan@yahoo.comBackground: Laparoscopic sacrohysteropexy is an emerging uterine-preserving strategy for management of uterovaginal prolapse (UVP). The literature on laparoscopic sacrohysteropexy for management of UVP is very scarce from Saudi Arabia. This research examined the feasibility, clinical utility, and safety of laparoscopic sacrohysteropexy in a Saudi setting.Methods: A retrospective study was conducted, including all patients who met the inclusion criteria. The laparoscopic sacrohysteropexy technique was adapted with modifications from the "Oxford hysteropexy". The primary endpoint was overall success, defined as anatomical success in all vaginal compartments (UVP grade 0 or 1 postoperatively). The secondary endpoint was the mean change in point C. Descriptive data were summarized with numbers and percentages, while numerical data used means ± standard deviations. Fisher's exact and Student's t tests were used for univariate analyses. Significant surgical outcome predictors were identified via logistic regression, with p < 0.05 considered statistically significant.Results: Overall, 21 patients met the inclusion criteria. The most frequent indication for laparoscopic sacrohysteropexy was UVP without anterior or posterior wall prolapse (n = 15, 71.4%), whereas the most frequent grade of UVP was grade III (n = 13, 61.9%). One patient (4.8%) required switch to laparotomy due to severe adhesions. No perioperative complications were recorded. The mean change in point C and hospital stay were 5.8 ± 2.1 (range: 0- 8) and 1.4 ± 0.6 days (range: 1- 3), respectively. Surgical success was achieved in 18 patients (85.7%). Only three patients experienced recurrences (one, two, and six months postoperatively). The mean change in point C was significantly higher in successful cases contrasted with the failed cases (6.5 versus 1.3).Conclusion: Laparoscopic sacrohysteropexy for management of uterovaginal prolapse revealed technical feasibility, safety, and beneficial utility of the procedure. Further large-sized and multicentric investigations are important to gather additional pertinent information on laparoscopic sacrohysteropexy.Keywords: pelvic organ prolapse, uterovaginal prolapse, sacrohysteropexy, surgical failure, success rate